2023
DOI: 10.1093/jmammal/gyad018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of the Vicuña (Lama vicugna) in a high Andean protected area

Abstract: The study of animal space use is fundamental to effective conservation and management of wildlife populations and habitats in a rapidly changing world, yet many species remain poorly described. Such is the case for the spatial ecology of the Vicuña–a medium-sized wild camelid that plays a critical role, both as a consumer and as prey, in the high Andean food web. We studied patterns of space use of 24 adult female vicuñas from April 2014 to February 2017 at the southern edge of its range. Vicuñas showed strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…Regarding conspecific tolerance [8] -"In contrast with previous studies, we found considerable evidence for tolerance of conspecifics from different families, especially while foraging [5,9]most vicuña seasonal core ranges in San Guillermo National Park overlapped with seasonal core ranges of other individuals, with very few exclusive core ranges. This was corroborated by visual observations recorded opportunistically (anecdotally) during the study period that revealed as many as five collared vicuñas from distinct family groups feeding in close proximity to each other on multiple occasions."…”
Section: Gps Methodology [8]contrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding conspecific tolerance [8] -"In contrast with previous studies, we found considerable evidence for tolerance of conspecifics from different families, especially while foraging [5,9]most vicuña seasonal core ranges in San Guillermo National Park overlapped with seasonal core ranges of other individuals, with very few exclusive core ranges. This was corroborated by visual observations recorded opportunistically (anecdotally) during the study period that revealed as many as five collared vicuñas from distinct family groups feeding in close proximity to each other on multiple occasions."…”
Section: Gps Methodology [8]contrasting
confidence: 99%
“…Regarding site fidelity [8]-"Vicuñas demonstrated high site fidelity, in line with previous studies that observed year-round maintenance of territories by vicuña families [5,9,10]. While this is a possibility, the differences in home range size could also result from methodological differences, since estimates from previous studies were based on a visual estimation of movements in the landscape rather than using quantitative home range estimation methods based on systematic data collection over sustained periods of time, as is possible with GPS collar data."…”
Section: Gps Methodology [8]mentioning
confidence: 99%
“…Pumas are ambush predators that hunt using cover provided by vegetation, uneven terrain, and rocks (Bank & Franklin, 1998). In SGNP, vicuñas occupy the same areas year‐round and graze in groups typically composed of a single male, three females (range 1–6), and two calves (range 1–4) (Karandikar et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Within these family groups, the male delimits and defends his territory with his harem against other males, while also herding the females when they move away from their territory (Vilá 1995(Vilá , 1999(Vilá , 2000; ARCMV-ANMIN Apolobamba 2022). While several studies have suggested that family groups occupy an area of ~18 ha, recent research indicates that this area may be much larger (~53 ha) (Vilá 1995(Vilá , 1999(Vilá , 2000; ARCMV-ANMIN Apolobamba 2022; Karandikar et al 2023).…”
Section: Study Speciesmentioning
confidence: 99%